PERLINDUNGAN KONSUMEN TERHADAP PRODUK SKINCARE OVERCLAIM DALAM JUAL BELI MELALUI E-COMMERCE MENURUT PERSPEKTIF HUKUM EKONOMI SYARIAH - Nuzumi Kailani; Nurul Fitria (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2025)
This article discusses consumer protection against overclaim skincare products marketed through e-commerce in Indonesia and examines overclaim practices from the perspective of Islamic economic law. Normatively, producers are expected to provide honest, transparent, and fair information regarding product ingredients in accordance with Law Number 8 of 1999 on Consumer Protection as well as the principles of Islamic economic law, which emphasize honesty (ṣidq), transparency (tablīgh), and justice (‘adālah). However, empirically, overclaim practices are still widespread, where the content of active ingredients such as niacinamide and retinol is significantly lower than what is claimed on the label. This condition causes real harm to consumers in the form of financial losses, skin health problems, and psychological stress that affects self-confidence. Therefore, this study emphasizes the importance of strengthening regulations, ensuring consistent law enforcement, and tightening supervision of products marketed online. In addition, consumer education through social media, universities, and beauty communities is essential to improve product literacy, enabling consumers to be more critical and discerning in evaluating product claims and making appropriate purchasing decisions.